Special issue: Restoration for whom, by whom? - Elias, Marlène; Joshi, Deepa; Meinzen-Dick, Ruth S. (University of Wisconsin Press, 2021)
The UN Decade on Ecosystem Restoration (2021–2030) frames restoration as a momentous nature-based solution for achieving many of the ecological, economic, and social objectives outlined in the Sustainable Development Goals. Yet, a critical void lies at the heart of this agenda: the lack of attention to social and political dimensions of nature and restoration initiatives. At this critical juncture, urgent attention is needed to the power and politics that shape the values, meanings, and science driving restoration; and to the uneven experiences of these processes as national restoration pledges touch down in diverse and unequal contexts. In this introduction to the special issue on “Restoration for Whom, by Whom?”, we critically examine the social inclusivity of restoration agendas, policies, and practices as these unfold across ecological and geographic scales. We argue that feminist political ecology (FPE), with its focus on gendered power relations, scale integration, and historical awareness, and its critique of the commodification of nature, offers a valuable lens through which to examine the socio-political and economic dynamics of restoration. Taking an FPE perspective, we elucidate how the ten papers comprising the special issue challenge mainstream narratives of environmental sustainability and suggest more grounded and nuanced ways forward for inclusive restoration initiatives. In conclusion, we highlight the urgency of addressing the systemic fault lines that create exclusions in restoration policies and practice; and the need to legitimize the plural voices, values, situated knowledges, and paths to sustainably transform degraded landscapes.